The association between adult IgA vasculitis and cancer: a prospective observational study - Hočevar, Alojzija; Jurčič, Vesna; Rotar, Žiga (Frontiers in Medicine, 2025)
ObjectivesCancer has been reported as a potential trigger for IgA vasculitis (IgAV) in adults; however, data on this topic are scarce. The aim of our study was to examine the frequency and location of cancer in adults with IgAV.MethodsWe included 295 IgAV patients diagnosed between January 2010 and June 2021 and followed at our secondary/tertiary rheumatology centre. Cancer episodes were recorded and classified into three groups according to their temporal relation to IgAV: (1) cancer diagnosed prior to IgAV; (2) cancer diagnosed concurrently with IgAV; and (3) cancer diagnosed during IgAV follow-up. The term IgAV associated with cancer (IgAV-CA) was used for IgAV cases presenting while cancer was active or diagnosed within a three-year period before or after the IgAV diagnosis.ResultsForty-seven IgAV patients (15.9%) developed a total of 56 different cancers. Of these, 43 cancers (76.8%) preceded the IgAV diagnosis, 3 cancers (5.3%) were diagnosed concurrently with IgAV, and 10 cancers (17.9%) were diagnosed during the IgAV follow-up. Twenty-two IgAV patients (7.5%) who developed a total of 24 cancers (42.9%) could be classified as IgAV-CA cases. The three most frequently diagnosed cancers in the IgAV-CA group were prostatic, renal and bladder cancer, together accounting for 50% of cancers. Age and smoking were associated with concurrent cancers, and arthritis represented a risk factor for cancer development during IgAV follow-up.ConclusionIgAV cases associated with cancer represent 7% of adult IgAV cases. In elderly patients, careful examination of the urogenital tract is warranted when cancer is suspected.